2022
DOI: 10.1093/ntr/ntac029
|View full text |Cite
|
Sign up to set email alerts
|

Biomarkers of Exposure and Biomarkers of Potential Harm in Adult Smokers Who Switch to e-Vapor Products Relative to Cigarette Smoking in a 24-week, Randomized, Clinical Trial

Abstract: Introduction Long-term health effects of e-vapor products (EVPs) are not well-established. We compared biomarkers of exposure (BoE) to select harmful and potentially harmful constituents (HPHCs) and biomarkers of potential harm (BoPH) in adult smokers (AS) who switched to EVPs vs continued smoking for 24 weeks. Methods AS (n=450, >10 cigarettes per day [CPD] for ≥10 years), were randomly assigned to continue smoking (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…All included studies reported urinary TSNA levels, with one also reporting on salivary levels. 34 Longitudinal studies included eight RCTs 35–42 two non-randomized intervention studies 43 , 44 and two observational studies. 45 , 46 Ten cross-sectional studies 34 , 47–55 were also included.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All included studies reported urinary TSNA levels, with one also reporting on salivary levels. 34 Longitudinal studies included eight RCTs 35–42 two non-randomized intervention studies 43 , 44 and two observational studies. 45 , 46 Ten cross-sectional studies 34 , 47–55 were also included.…”
Section: Resultsmentioning
confidence: 99%
“…In eight RCTs where people who smoked at baseline switched to vaping, NNAL was reduced significantly, in four short-term studies 37 , 39 , 40 , 42 by 55% to 68%, and in four medium-term studies by 53% to 95% 35 , 36 , 38 , 41 ( Table 1 ). Short-term use studies, which ranged from five to seven days, were all conducted in research facility where access to tobacco cigarettes or e-cigarettes were controlled by the research team.…”
Section: Smoking Versus Vapingmentioning
confidence: 99%
See 1 more Smart Citation
“…NGP-related biomarkers, both BOE and BOBE, can be beneficially applied in a number of ways and in a range of fields. As mentioned above, they have been used to assess the tobacco harm reduction potential of NGPs, particularly BOE but also BOBE, 23,[27][28][29][30][31][32] Biomarker data are now forming useful contributions among many lines of evidence indicating appropriateness for the protection of public health in NGP regulatory submissions. In the United States, such studies have been instrumental in the marketing authorizations being granted to selected HTPs, a few ECs, but as yet no NPs.…”
Section: Application Of Ngp-related Biomarkersmentioning
confidence: 99%
“…NGP‐related biomarkers, both BOE and BOBE, can be beneficially applied in a number of ways and in a range of fields. As mentioned above, they have been used to assess the tobacco harm reduction potential of NGPs, particularly BOE but also BOBE, 23,27–32 in cross‐sectional, longitudinal, and switching studies.…”
Section: Application Of Ngp‐related Biomarkersmentioning
confidence: 99%